Ergonomic factors of risk for agricultural workers in the northern area of Cartago, Costa Rica - Madriz-Quirós, Carmen Elena (2021)
Agriculture is one of the productive activities that involves a lot of ergonomic exposure. Musculoskeletal injuries are frequently developed among male population who are high involve in this activity.  This study shows and quantifies the potential of ergonomic risks in agriculture tasks where awkward postures, high repetitions,  load handling, and long working hours affect the health of farm workers. The planting rotation conducts to high ergonomic exposure in carrots, potatoes and lettuces farming, which increases the risk of injuries, mainly in bodily areas such as the lower back, knees and shoulders, and in second order, in hands and wrists. These results demand intervention with new tools and work organization.